Plant traits poorly predict winner and loser shrub species in a warming tundra biome - García Criado, Mariana; Myers-Smith, Isla H; Bjorkman, Anne D; Normand, Signe; Blach-Overgaard, Anne; Thomas, Haydn J D; Eskelinen, Anu; Happonen, Konsta; Alatalo, Juha M; Anadon-Rosell, Alba; Aubin, Isabelle; Te Beest, Mariska; et al. (Nature communications, 2023)
Climate change is leading to species redistributions. In the tundra biome, shrubs are generally expanding, but not all tundra shrub species will benefit from warming. Winner and loser species, and the characteristics that may determine success or failure, have not yet been fully identified. Here, we investigate whether past abundance changes, current range sizes and projected range shifts derived from species distribution models are related to plant trait values and intraspecific trait variation. We combined 17,921 trait records with observed past and modelled future distributions from 62 tundra shrub species across three continents. We found that species with greater variation in seed mass and specific leaf area had larger projected range shifts, and projected winner species had greater seed mass values. However, trait values and variation were not consistently related to current and projected ranges, nor to past abundance change. Overall, our findings indicate that abundance change and range shifts will not lead to directional modifications in shrub trait composition, since winner and loser species share relatively similar trait spaces.
Keywords: tundra; semena rostlinná; Phenotype; Seeds; Climate Change; ekosystém; fenotyp; Ecosystem; Tundra; klimatické změny